MYH biallelic mutation can inactivate the two genetic pathways of colorectal cancer by APC or MLH1 transversions. - Lefevre, J; Colas, C; Coulet, F; Bonilla, C; Mourra, N; Flejou, J; Tiret, E; Bodmer, W; Soubrier, F; Parc, Y (2010)
MYH associated polyposis is a hereditary syndrome responsible for early colorectal cancer with a distinct genetic pathway from the Familial Adenomatous Polyposis or the Hereditary Non Polyposis Colorectal Cancer syndrome. We have studied a family with three members bearing a biallelic mutation in MYH at c.1185_1186dup. One patient who developed colon cancer had loss of expression of MLH1 on tumoral tissue and microsatellite instability (MSI) phenotype. Analysis of MLH1 based on his blood sample revealed no germline mutation or large genomic deletion. No methylation of the promoter was identified in tumoral DNA. No transversion mutations were identified in APC or KRAS in tumor DNA of this patient. Loss of expression of MLH1 was due to a transversion in intron 7 at position +5 (c.588 + 5G > T) leading to a complete deletion of exon 7 at the RNA level. This observation demonstrates that MLH1 can be a target of MYH transversions leading to MSI phenotype.